024 Matrix marking system: a future for debrief and assessment. (14th September 2011) - Hanson, J; Pimblett, M; Dickinson, M; Jones, G; Davis, M
Abstract : Objectives and Backgrounds: Medical error accounts for 40 000 deaths per year in the UK, of which 50% are regarded as preventable. There is currently a greater emphasis on patient safety in medical practice; the practice of medicine is dependent on human cognition and although medical error is inevitable, training in both technical and non-technical skills can minimise this. Simulation enables practice in a safe environment and debrief is vital in these skills. The aim of this session is to describe a debrief system which enhances real-time marking through instant video feedback of performance in both technical and non-technical skills. Methods: Initially analogue video systems were used for feedback. Identifying elements for debriefing was time-consuming and unreliable. Using digital recording systems integrated with Studiocode software, we are able to capture elements of a scenario directly onto a hard drive. I Coda software, initially developed to analyse sports performance, is used to code performance against templates developed for specific clinical scenarios. Both technical and non-technical performance can be observed, analysed and coded using an iPad or PDA. This has been developed as a portable system to facilitate observations in theatres, hospital transfers or other clinical environments. Results: The Matrix Marking System provides opportunities for instantaneous debriefing after the simulation event in both technical and non-technical skills, based on performance evidence. The facilitator has access to a summary of ratings of performance and an opportunity to replay these for exploration and further analysis. Conclusions: This brings a new dimension to the debriefing of individual or team performance. The learning conversation (debrief), which develops can be highlighted with instant video feedback to reinforce points for discussion. This system is undergoing validation for debriefing and assessments. We will be looking to report on progress in future meetings.